Tax credits and intergovernmental fiscal relations - Maxwell, James Ackley (Washington, D.C. : Brookings Institution, 1962)
This book is a study that examines the proposals for new or enlarged grant-in-aid for particular activities that is the demand for additional federal financial assistance to state-local governments.
Includes bibliographical references and index.
gp 24/01/2019
Loans
Keywords: Income tax deductions; Intergovernmental fiscal relations